Clues from crystal structures pave the way to access chiral myo-inositol derived versatile synthons: resolution of racemic 4-o-allyl-myo-inositol-1,3,5-orthoesters via corresponding dicamphanates by crystallization - Patil, Nivedita T.; Shashidhar, Mysore S.; Tamboli, Majid I.; Gonnade, Rajesh G. (Crystal Growth & Design, 2017)
Racemic 4-O-allyl-myo-inositol-1,3,5-orthoesters were resolved as the corresponding diastereomeric dicamphanates by crystallization from alcoholic solvents. Crystals of the two diastereomers of myo-inositol orthoacetate and one diastereomer each of myo-inositol orthoformate and myo-inositol orthobenzoate were obtained in >99% purity, on gram scale. The configuration of all these diastereomers was established by conversion to known chiral myo-inositol derivatives as well as by single crystal structure analysis. It is interesting to note that the procedures for the separation of diastereomeric myo-inositol orthoesters could be evolved due to the knowledge of crystal growth and crystal structures of inositol derivatives of comparable molecular structures. Due to the synthetic versatility of myo-inositol orthoesters, the methods described provide rapid and convenient access to a variety of chiral inositol derivatives with high synthetic potential.

Access to enantiomeric organic compounds with potential for synthesis via racemic conglomerates: inositol derivatives as a case in point - Patil, Nivedita T.; Patil, Madhuri T.; Sarkar, Nitai; Gonnade, Rajesh G.; Shashidhar, Mysore S. (Crystal Growth & Design, 2021)
The crystal structure database was used to identify inositol derivatives that could be crystallizing as racemic conglomerates. Among the six racemic inositol derivatives identified, racemic 4-O-tosyl-6-O-benzyl-myo-inositol-1,3,5-orthoformate (A) was found to be a true conglomerate and was resolved on the multigram scale by the preferential crystallization technique. This resolution procedure does not require the use of any enantiomeric resolving agent. The resolved enantiomers of A are useful for the synthesis of natural and unnatural enantiomeric derivatives of inositol, since they carry orthogonal hydroxy protecting groups. Racemic 4-O-methanesulfonyl-myo-inositol-1,3,5-orthoformate (B) on crystallization from common organic solvents generally yielded racemic twin crystals, while in the presence of structural analogs as additives, they yielded true racemic crystals. A comparison of the crystal structures of the true racemate, twinned crystal and crystal of one of the enantiomers of B, revealed the reasons for the formation of polymorphic (twin) crystals. Such instances are relatively rarely encountered but nevertheless shed light on our understanding of polymorphism and twinning of crystals.

Asymmetric synthesis of inositol derivatives - Patil, Nivedita T.; Sarkar, Nitai; Mysore, S. Shashidhar; Gonnade, Rajesh G. (Tetrahedron, 2024)
Both the enantiomers of racemic 4- O -tosyl-6- O -benzyl- myo -inositol-1,3,5-orthoformate ( 2 ) were isolated by preferential crystallization and used to synthesize several enantiomeric myo -inositol derivatives - natural ononitol, natural laminitol, precursors for myo -inositol phosphates and an oxabicyclo [2.2.1] heptane derivative. This work demonstrates the potential of the enantiomeric tosylates D2 and L2 to serve as versatile starting materials for the absolute asymmetric synthesis of inositol derivatives and other natural products from symmetric myo -inositol since no optically active molecular entity was required for the resolution of 2.
Keywords: Asymmetric synthesis; Carbohydrate; Cyclitol; Inositol; Natural product

Desymmetrization of myo-inositol - Patil, Nivedita T.; Patil, Madhuri T.; Gonnade, Rajesh G.; Shashidhar, Mysore S. (Carbohydrate Research, 2025)
Chemistry and biology of phosphoinositols have been intensely investigated areas of research over the last 4-5 decades due to their involvement in cellular signal transduction pathways. Efficient laboratory synthesis of enantiomeric derivatives of inositols was a central issue since they were required for the delineation of the myo-inositol cycle as well as for the total synthesis of polyol based natural products and their derivatives. This essentially meant the development of competent methods for the desymmetrization of myo-inositol leading to the preparation of enantiomeric O-substituted derivatives of myo-inositol. This was approached by: the classical resolution methods involving separable diastereomers, the chiral pool synthesis, enzyme catalysis, asymmetric catalysis and preferential crystallization of enantiomers in a racemic conglomerate. This review summarizes results obtained in author's laboratory, as well as those reported in the literature on attempts at desymmetrization of myo-inositol.
Keywords: Conglomerate; Crystallization; Cyclitol; Enantiomers; Inositol; Lipid